1998
DOI: 10.1177/08959374980120011001
|View full text |Cite
|
Sign up to set email alerts
|

Topically Applied Cmt-2 Enhances Wound Healing in Streptozotocin Diabetic Rat Skin

Abstract: Delayed wound healing is one of the complications of diabetes mellitus, exhibited by increased wound collagenase and decreased granulation tissues. The current study compared wound healing in normal and diabetic rats, and the effects of topically applied 1% or 3% concentrations of chemically modified tetracycline-2 (CMT-2) on 6-mm circular full-thickness skin wounds healed by secondary intention. On day 7 after wounding, tissues were removed for biochemical analysis and histology. The wound granulation tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…Intrinsic factors comprising cell-surface receptors, growth factors such as platelet-derived growth factor (PDGF), insulin-like growth factor (IGF-1), transforming growth factor (TGF-β), and cell adhesion molecules such as integrins play a significant role in the coordination of intricate events during normal wound healing. 19 Diabetes is one of the factors affecting the normal course of wound healing. Diabetic wound healing is characterized by a delay in cellular infiltration and formation of granulation tissue, decreased wound collagen content, diminished wound tensile strength and prolonged epithelialization time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrinsic factors comprising cell-surface receptors, growth factors such as platelet-derived growth factor (PDGF), insulin-like growth factor (IGF-1), transforming growth factor (TGF-β), and cell adhesion molecules such as integrins play a significant role in the coordination of intricate events during normal wound healing. 19 Diabetes is one of the factors affecting the normal course of wound healing. Diabetic wound healing is characterized by a delay in cellular infiltration and formation of granulation tissue, decreased wound collagen content, diminished wound tensile strength and prolonged epithelialization time.…”
Section: Discussionmentioning
confidence: 99%
“…Full-thickness cutaneous wounds which heal by secondary intention form granulation tissue which serves to fill the dermal defect and provide a structural framework for the deposition of newly synthesized collagen. 19 The fullthickness wound in diabetic rats is clinically relevant and comparable with impaired wound healing in human diabetes mellitus. 27 In this study, the rate of wound contraction was significantly (p<0.05) reduced in diabetic controls; MC extract showed better rate of wound contraction at 400 mg/kg oral dose.…”
Section: 21mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the activities of MMP‐2 and MMP‐9 were shown to be increased in diabetic healing‐impaired mice when compared with non‐diabetic non‐healing‐impaired mice 8 . Topical application of chemically modified tetracycline‐2, an inhibitor of MMP activity, enhanced wound healing in diabetic rats 9 . These data indicate that elevated levels of MMPs may impair wound healing.…”
mentioning
confidence: 94%
“…Tetracycline and its non‐antimicrobial derivative, CMT‐8, are able to inhibit bone loss in ovariectomized rats (for review see Sasaki et al 3). A recent study by Ramamurthy et al 4 has shown enhanced wound healing in diabetic rats with topically applied CMT‐2. In this study we describe the effect of oral administration of CMT‐8 or estrogen on the healing of skin wounds in aged female rats, 120 days post ovariectomy (OVX).…”
Section: Introductionmentioning
confidence: 99%